Isolated Angiitis of the CNS - J Gordon Millichap (Pediatric Neurology Briefs)
The clinical features, pathology, and outcome of isolated (primary, idiopathic) angiitis of the CNS (IACNS) in two new and 8 previously reported cases are analysed at the Hospital for Sick Children, Toronto, Canada.